Utilization of Medications With Cognitive Impairment Side Effects and the Implications for Older Adults' Cognitive Function. (October 2020) - Do, Duy; Schnittker, Jason
Objectives: Many medications have cognitive impairment, memory loss, amnesia, or dementia as side effects ("cognitive side effects" hereafter), but little is known about trends in the prevalence of these medications or their implications for population-level cognitive impairment.Method: We use data from the National Health and Nutrition Examination Survey (1999–2016) to describe trends in the use of medications with cognitive side effects among adults aged 60+ ( N = 16, 937) and their implications for cognitive functioning (measured using word learning and recall, animal fluency, and digit symbol substitution assessments).Results: Between 1999 to 2000 and 2015 to 2016, the prevalence of older adults taking one, two, and at least three medications with cognitive side effects increased by 10.2%, 57.3%, and 298.7%, respectively. Compared to non-users, respondents who simultaneously used three or more medications with cognitive side effects scored 0.22 to 0.27 standard deviations lower in word learning and recall ( p = .02), digit symbol substitution ( p < .01), and the average standardized score of the three assessments ( p < .001).Limitation: Dosage of medications associated with cognitive side effects was not measured.Discussion: Concurrent use of medications with cognitive side effects among older adults has increased dramatically over the past two decades. The use of such medications is associated with cognitive impairment and may explain for disparities in cognitive function across subgroups. These findings highlight the need for cognitive screenings among patients who consume medications with cognitive side effects. They also highlight the synergic effects of polypharmacy and potential drug-drug interactions that result in cognitive deficits.